Psychometric properties of the Ambivalent Sexism Inventory in Peruvian students - Manrique Tapia, César Raúl (2020)
The present investigation was oriented to establish the psychometric properties of the Inventory of ambivalent sexism (ASI) in young people from technical educational institutions of the Huaral district, the type of study that was used was instrumental, we worked with a census sample, which included 1000 students, from ages between 18 to 30 years. The inventory items analysis was performed, yielding values greater than 0.3, the exploratory factor analysis (EFA) was performed, where the union of 5 factors was demonstrated, which show 51.1% of the total variance. the confirmatory factor analysis (CFA) of the second order, where good adjustment indices are evident, in addition, an adequate inventory reliability was obtained, Cronbach's alpha coefficient of 0.868 and Omega coefficient of 0.869. In conclusion, it was established that the ASI has adequate psychometric properties, and it turns out to be a valid and reliable instrument for its application within the established population.